Gambaran Hematologi Tikus Putih (Rattus norvegicus) yang Diinfeksi Escherichia coli Enteropatogenik dan Diberikan Probiotik - M Astawan; T Wresdiyati; I I Arief; E Suhesti (Media Peternakan, 2011)
In Indonesia, diarrhea is the second leading cause of death in children after ISPA (Acute Respiratory Infection). This study aimed to test the ability of probiotic, Lactobacillus plantarum 2C12 and Lactobacillus acidophilus 2B4, as an indigenous anti-diarrhea in rats exposed to Enteropathogenic Escherichia coli (EPEC) and find out their impact on erythrocytes, hematocrit, hemoglobin, thrombocytes, and leukocytes. A total of 95 male rats Sparague Dawley strain were alocated into six treatment groups: (1) negative control, (2) L. plantarum 2C12, (3) L. acidophilus 2B4, (4) L. plantarum 2C12 + EPEC, (5) L. acidophilus 2B4 + EPEC, and (6) positive control (exposed to EPEC). Probiotics were given from day 1 up to 21, whereas 106 cfu/ml EPEC was administered orally from day 8 to 14. On day 21, the number of erythrocytes, hematocrit and hemoglobin were the lowest (7.07 million/µl; 39.13%; 14.50 g/dl) in the positive group of rats. The positive control group had lower number of thrombocytes (389 thousand/ µl) (P < 0.05) with the negative control and the L. plantarum 2C12 groups, but not significantly different to the other groups. The number of leucocytes in the positive control rats (4433 cell/µl) was lower (P < 0.05) than that of the negative control, L. plantarum 2C12, and the L. acidophilus 2B4 groups, but no significant difference to the other groups. L. plantarum 2C12 had better ability than L. acidophilus 2B4 in maintaining the number of erythrocytes, hematocrit, and hemoglobin of rat infected by EPEC.